Enhanced Photoreversible Color Switching of Redox Dyes Catalyzed by Barium‐Doped TiO2 Nanocrystals1. (19th January 2015) - Wang, Wenshou; Ye, Yifan; Feng, Ji; Chi, Miaofang; Guo, Jinghua; Yin, Yadong
Abstract Colloidal barium‐doped TiO2 nanocrystals have been developed that enable the highly reversible light‐responsive color switching of redox dyes with excellent cycling performance and high switching rates. Oxygen vacancies resulting from the Ba doping serve as effective sacrificial electron donors (SEDs) to scavenge the holes photogenerated in TiO2 nanocrystals under UV irradiation and subsequently promote the reduction of methylene blue to its colorless leuco form. Effective color switching can therefore be realized without relying on external SEDs, thus greatly increasing the number of switching cycles. Ba doping can also accelerate the recoloration under visible‐light irradiation by shifting the absorption edge of TiO2 nanocrystals to a shorter wavelength. Such a system can be further casted into a solid film to produce a rewritable paper on which letters and patters can be repeatedly printed using UV light and then erased by heating; this process can be repeated for many cycles and does not require additional inks.